Grid-connected photovoltaic-based microgrid as charging infrastructure for meeting electric vehicle load - Chowdary, Appalanaidu; Rao, Sura Srinivasa (Frontiers in Energy Research, 2022)
Abstract: Concerns about charging infrastructure have arisen as electric vehicles (EV) gain popularity in the transportation sector. Like gas stations, the charging infrastructure is mainly used to power the electric vehicle's batteries until they get full charged. As a result, many alternative options for creating charging stations were being explored in the literature. This paper proposes a grid-connected photovoltaic-based microgrid for EV charging infrastructure. This study has two objectives: one is the design and modelling of grid-connected photovoltaic-based microgrid; the second is the analysis considering a hypothetical population of EVs. While modelling, the realistic EV loads are considered, and the simulation is carried out. Results of this study include the power generation potential from the solar power plant, energy mix of the microgrid, i.e., grid shared energy and onsite solar generation, and supply and load mismatch relationships. The analysis results include the weather parameter influence on power produced, followed by sensitivity analysis. Overall, it is understood that grid-connected microgrids support the seamless charging of EVs even in the case of uncertainties observed with onsite solar energy generation.